EVALUATING COMBINING ABILITIES AND HETEROTIC EFFECTS FOR ENHANCED COTTON YIELD - RASHEED, Z; ANWAR, MR; HANIF, K; ADREES, A; KARIM, WA; AMJAD, K; HASSAN, A; MAZHAR, HSUD; TIPU, ALK; KHAN, TM (Biological and Clinical Sciences Research Journal, 2023)
The present research was conducted to evaluate heterosis in diallel crosses, determining general and specific combining abilities for yield-related traits and identifying top-performing genotypes for future breeding programs. A field experiment was conducted using selected genotypes (CIM-599, CIM-602, Shahkar, and NS-181) to produce F1 hybrids through frequent pollinations in a diallel fashion. Twelve F1 hybrids and their four parental genotypes were cultivated in a randomized complete block design with two replications. Yield-related traits including plant height, branches per plant, bolls per plant, lint percentage, boll weight, seed cotton yield, seed index, and lint index were recorded. Analysis of variance and combining ability effects analysis were performed to assess the significance of the genotypes and their interactions. Significant variability among parental genotypes was observed for yield-related traits, indicating genetic variation in the breeding material. Combining ability analysis revealed the predominance of non-additive gene action. General combining ability (GCA) effects were significant for most traits, with CIM-599 exhibiting the highest GCA effects. Specific combining ability (SCA) and reciprocal combining ability (RCA) effects were significant for various traits and hybrid combinations, indicating their potential for trait improvement. Notably, the hybrid combination CIM-599 x Shahkar exhibited substantial mid-parent heterosis for seed cotton yield, boll weight, and lint percentage. This cross also displayed notable SCA effects, indicating its importance for hybrid breeding. These findings highlight the potential of hybrid breeding for trait enhancement. Future breeding programs could leverage the insights gained here to create improved cotton varieties with enhanced yield.